A pH-responsive PROTAC-based nanosystem triggers tumor-specific ferroptosis to construct in situ tumor vaccines - Linghong Huang; Xinyuan Sun; Qinhua Zuo; Ting Song; Ning Liu; Zonghua Liu; Wei Xue (Materials Today Bio)
Bromodomain-containing protein 4 (BRD4) is a key protein that drives the development of malignant melanoma and is closely associated with the ferroptosis signaling pathway. Degradation of BRD4 can downregulate the expression of ferroptosis-related genes such as GPX4, thereby promoting tumor-specific ferroptosis. Therefore, targeting BRD4 for degradation is a promising strategy for inhibiting tumor growth. We constructed a PROTAC drug-based tumor antigen capture system to protect the activity of antigen-presenting cells (APCs) and promote antigen capture. The selected PROTAC drug (ARV-825) can specifically degrade BRD4 without harming immune cells. Specifically, magnetic nanoclusters (MNC) coated with calcium-doped manganese carbonate (Ca/MnCO3), were used to load PROTAC drug (ARV-825) and anti-PD1, forming the MNC@Ca/MnCO3/ARV/anti-PD1 system. ARV-825 can specifically degrade BRD4 and GPX4, significantly inducing ferroptosis in tumor cells and releasing tumor-associated antigens. The MNC@Ca/MnCO3 particles, with their large specific surface area, adsorbed the tumor antigens, preventing antigen loss and enhancing antigen presentation. Additionally, Mn2+ served as an adjuvant to promote the maturation and cross-presentation of APCs. Together with the PD1 antibody, this further enhanced the anti-tumor response of the in situ tumor vaccine and reversed the suppressive immune microenvironment. This antigen capture system provides a novel strategy to improve the anti-tumor efficacy of in situ tumor vaccines.